A comparison of suicide notes written by men and women. Issue 3 (15th March 2016) - Lester, David; Leenaars, Antoon
ABSTRACT: Previous research using small samples and subjective judgments has failed to identify reliable gender differences in suicide notes. Suicide notes written by 166 women and 513 men collected by Edwin Shneidman were analyzed by the Linguistic Inquiry and Word Count computer program. Six significant differences and four trends were identified. The suicide notes written by women had a higher percentage of words found in the dictionary, negations, words indicative of cognitive process, discrepancies and present tense verbs. The suicide notes of women seemed to have more content indicative of hopelessness, defeat-entrapment and falling short of internalized standards.